Status of quality of training activities and needs of renovation of some training programs for science-technology andministration - Nghi, Nguyen Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
The study presents the status of quality of training activities and needs of renovation of some training programs for science-technology administration for higher level of quality of training activities and human resources for science-technology administration. The paper also provides results of survey for assessment of the status of some short term training programs for science-technology administration. At the same time, the paper identifies needs for renovation of training programs and methods of organization of implementation, administration and monitoring works of quality of training works for science-technology administration. On basis of that, the paper identifies needs of renovation of training programs to meet requirements of development. Code: 19071501